The Influence of Passive Ultrasonic Irrigation Associated with Different Irrigating Solutions on Radicular Dentin Microhardness - Nogueira, Sandra Pillon; Bueno, Carlos Eduardo da Silveira; Martin, Alexandre Sigrist De; Pelegrine, Rina Andrea; Fontana, Carlos Eduardo; Pinheiro, Sérgio Luiz (Archives of Clinical and Biomedical Research, 2020)
Introduction: This study’s aim was to evaluate the effects of irrigating solutions with 2% chlorhexidine gluconate (CHX) 17% ethylenediaminetetraacetic acid (EDTA), and 2.5% sodium hypochlorite (NaOCl) on root dentin microhardness. Methods: Eighty mesiobuccal canals from lower molars were irrigated with conventional irrigation(CI) or passive ultrasonic irrigation (PUI). The roots were divided into eight groups: CHX+CI; CHX+PUI; EDTA+CI; EDTA+PUI; NaOCl+CI; NaOCl+PUI; distilled water (DW)+CI; DW+PUI. The Knoop microhardness test was used to evaluate indentations at 100 μm and 500 μm in the cervical, middle and apical thirds. The results were analyzed with the Kruskal-Wallis (Dunn) test. Results: At 100 μm in the cervical third, the highest and lowest values were found in the CHX+PUI Group and EDTA+PUI groups, respectively (P<0.05). In the middle third, the highest and lowest values were found in the CHX+CI and EDTA+PUI groups, respectively (P<0.05). In the apical third, the highest and lowest values were found in the CHX+CI and EDTA+CI groups, respectively (P<0.05). At 500 μm in the cervical third, the highest and lowest values were found in the NaOCl+PUI and EDTA+PUI groups, respectively (P<0.05). In the apical third, the highest and lowest values were found in the NaOCl+PUI and EDTA+CI groups, respectively (P<0.05). Conclusion: Dentin microhardness was affected by these irrigating solutions. There was a greater reduction of microhardness in the cervical and middle thirds with 17% EDTA plus PUI. When associated with PUI, 2% CHX and 2.5% NaOCl had no impact on microhardness.